Super-corrosion-resistant high-entropy alloy with nano precipitated phase and preparation method of super-corrosion-resistant high-entropy alloy
By developing Al0.4FeNi2.2Cr0.9V0.2 high-entropy alloy and adjusting its aging heat treatment time, the FCC phase and Ni3Al-type nano-precipitation phase are formed, which solves the problem of insufficient corrosion resistance of high-entropy alloys in seawater environments, and significantly improves the The corrosion resistance and hardness of the material have excellent application prospects.
Patent Information
- Application Number
- CN202411359448.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing high-entropy alloys have shortcomings in corrosion resistance, especially in seawater environments. If the addition of Al, Mo, Ti and other elements exceeds a certain content, the corrosion resistance will drop sharply, and the lack of system components-structure-corrosion Performance correlation study.
Al0.4FeNi2.2Cr0.9V0.2 high-entropy alloy was developed, and its precipitation phase structure and hardness were improved by adjusting the aging heat treatment time, forming an FCC phase and a Ni3Al nano-precipitation phase, significantly improving its in 3.5 wt.% NaCl solution Corrosion resistance.
The excellent corrosion resistance of Al0.4FeNi2.2Cr0.9V0.2 high-entropy alloy in seawater environment is achieved, the corrosion current density is lower than 9.348×10-7A/cm2, and the hardness value of the material is increased to 300-350HV, with Good application prospects.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a seawater corrosion resistant Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The invention discloses a high entropy alloy material and a preparation method thereof, belonging to the technical field of new alloy materials and preparation methods thereof. Background Art
[0002] High entropy alloy is a new alloy system. Its unique composition and structural characteristics make it have better comprehensive properties than traditional structural materials. For example, studies have shown that high entropy alloys have outstanding mechanical properties such as high strength, high toughness, and good wear resistance, making it a potential structural material and a research hotspot. At the same time, some high-entropy alloy systems containing easily passivated alloying elements such as Cr and Ni have also been reported to have good corrosion resistance. In the process of developing new alloy materials, corrosion resistance is an important factor that must be considered. In 2005, Chen et al. reported that the CuxNiAlCoCrFeSi high entropy alloy has better uniform corrosion resistance than traditional 304 stainless steel in salt water and acidic environments, indicating the potential application value of high entropy alloys as corrosion-resistant structural materials.
[0003] At present, the research on the corrosion resistance of high entropy alloys is still in its infancy. Researchers hope to further improve the corrosion resistance of high entropy alloys by adding corrosion-resistant elements, such as Al, Mo, Ti, etc., and the addition of alloying elements such as Al and Ti can also make the high entropy alloy lightweight, and can further improve the tensile strength and hardness of the alloy. However, studies have shown that the addition of elements such as Al, Mo, and Ti will cause the corrosion resistance of high entropy alloys to drop sharply when exceeding a certain content, which is related to the structural transformation of the alloy caused by the addition of elements, and there is currently a lack of systematic research on the correlation between the composition-structure-corrosion performance of corrosion-resistant high entropy alloys. At present, there is no report on high entropy alloys based on the AlFeNiCrV system, so the development of Al with excellent corrosion resistance is still in the works. 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloys are of great significance to the development of high entropy alloys and the exploration of high corrosion resistance. Summary of the invention
[0004] The purpose of the present invention is to develop an Al2O3 alloy having excellent seawater corrosion resistance. 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, while improving Al by adjusting the aging heat treatment time 0.4 FeNi 2.2 Cr 0.9 V0.2 The invention discloses the precipitation phase structure, hardness and corrosion resistance of high entropy alloy, and also provides the corresponding preparation method.
[0005] The technical solution of the present invention is as follows:
[0006] A corrosion-resistant Al-Fe-Ni-Cr-V series high entropy alloy, characterized in that the high entropy alloy composition is Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 , including Al 8.5%, Fe 21.3%, Ni 46.8%, Cr 19.1%, and V 4.3%.
[0007] Further, the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The phase composition characteristics of the high entropy alloy are FCC phase and Ni3Al type nano-precipitation phase, showing the characteristics of uniform dispersion distribution.
[0008] Furthermore, the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloys have good hardness, with a hardness value of 300-350HV.
[0009] Furthermore, the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy exhibits excellent corrosion resistance in 3.5wt.% NaCl solution, with a corrosion current density lower than 9.348×10 -7 A / cm 2 .
[0010] As mentioned above, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 A method for preparing a high entropy alloy, characterized in that it comprises the following steps:
[0011] Step 1, ultrasonic cleaning and material weighing: 0.4 FeNi 2.2 Cr 0.9 V 0.2 Preparation of high entropy alloy Al, Fe, Ni, Cr, and V are placed in containers respectively, and firstly cleaned by oscillating with acetone solution in an ultrasonic oscillating device for 10-20 minutes, and then the same operation is performed with anhydrous ethanol, and finally the materials are blown dry for use; the Al 0.4FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was converted into corresponding weight according to atomic percentage and weighed, including Al 8.5%, Fe 21.3%, Ni 46.8%, Cr19.1%, and V 4.3%;
[0012] Step 2: Melting: Place the material in step 1 into a WK-Ⅱ vacuum arc furnace and use a mechanical and molecular pump to evacuate to 1-5×10 -4 Pa, then slowly fill in argon gas to make the vacuum degree reach 1~5×10 4Pa, and adjust the vacuum degree of the arc furnace to 1~5×10 -4 Pa; repeat this process 3 times to ensure that there is no oxygen in the vacuum chamber. Finally, slowly introduce argon gas to -0.02~-0.05Mpa, and melt the material at an arc current of 180~300A for 50-100s;
[0013] Step 3: Repeat the smelting several times according to the requirements of step 2 to ensure uniform composition, and cool for 10-30 minutes to obtain Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0014] Furthermore, the Al obtained in step 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is heat treated. The specific steps are: (1) melting the rod-shaped Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was homogenized at 1200 °C for 12 h in an Ar gas atmosphere and then quenched in water.
[0015] (2) The material in step 1 was cold rolled to 80%, cut into standard specimens of 10×10×3 mm, annealed at 1100° C. for 10 min, and then water quenched.
[0016] (3) The samples in step 2 were aged at 750°C for 1 / 2 / 4 / 10 h respectively and air-cooled to obtain the final high-hardness and super-corrosion-resistant Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0017] The present invention provides an Al2O3 super seawater corrosion resistant 0.4 FeNi 2.2 Cr 0.9 V 0.2High entropy alloys can improve Al by adjusting the aging heat treatment time. 0.4 FeNi 2.2 Cr 0.9 V 0.2 Microstructure, precipitation phase characteristics, hardness and corrosion resistance of high entropy alloys. 0.4 FeNi 2.2 Cr 0.9 V 0.2 The phase composition characteristics of high entropy alloys are FCC phase and Ni3Al type nano-precipitation phase, showing the characteristics of uniform dispersion distribution. 0.4 FeNi 2.2 Cr 0.9 V 0.2 Annealing twins are formed in the high entropy alloy, the size of the precipitated phase increases, the shape is more uniform, and the existence of the precipitated phase also plays a role in refining the grains, which not only improves the hardness of the high entropy alloy, but also significantly improves the corrosion resistance of the high entropy alloy in a 3.5wt.% NaCl solution. The high entropy alloy uses raw materials with a purity of not less than 99.9wt.%, and its form is small blocks or particles.
[0018] The advantages of the present invention are:
[0019] (1) Al of the present invention 0.4 FeNi 2.2 Cr 0.9 V 0.2 The grains in the high entropy alloy are refined, and the formation of precipitation phase improves the microstructure and properties of the high entropy alloy;
[0020] (2) Al of the present invention 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy has a simple FCC phase and a Ni3Al-type nano-precipitation phase, showing the characteristics of uniform dispersion distribution.
[0021] (3) Al of the present invention 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy has excellent corrosion resistance in 3.5wt.% NaCl solution, its corrosion current density is lower than 9.348×10-7A / cm2 and has obvious passivation zone. It has good application prospects in chemical production and petroleum equipment industry.
[0022] (4) Al of the present invention 0.4 FeNi 2.2 Cr 0.9 V 0.2High entropy alloys have good hardness, and the generation of precipitation phases effectively improves the hardness of high entropy alloys, with a hardness value of 300-350HV. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 XRD pattern of high entropy alloy;
[0024] Figure 2 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 Microstructure diagram of high entropy alloy, where (a), (b), (c) represent IPF diagrams after aging for 1, 2, and 4 h, respectively, and (d), (e), (f) represent phase diagrams after aging for 1, 2, and 4 h, respectively;
[0025] Figure 3 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 Hardness distribution diagram of high entropy alloy;
[0026] Figure 4 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 EDS images of high entropy alloys, where (a), (b), (c), (d), and (e) represent the EDS spectra of Al, Fe, Ni, Cr, and V elements, respectively.
[0027] Figure 5 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 Polarization curves of high entropy alloys in 3.5wt.% NaCl solution.
[0028] Figure 6 The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 Precipitation phase morphology of high entropy alloys at different aging times, where (a), (b), and (c) represent aging for 1, 2, and 4 h, respectively. Specific implementation methods
[0029] The Al of the present invention is described below in conjunction with the embodiments and drawings. 0.4 FeNi 2.2Cr 0.9 V 0.2 The high entropy alloy is further described, but the protection scope of the present invention is not limited to the contents of the embodiments.
[0030] Embodiment 1:
[0031] Preparation of Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, in which the atomic percentages of the elements are as follows: Al 8.5%, Fe 21.3%, Ni 46.8%, Cr 19.1%, V 4.3%.
[0032] Step 1: Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The materials for preparing high entropy alloy (Al material, Fe material, Ni material, Cr material, V material) are placed in glass beakers respectively, and firstly, they are cleaned by oscillating in an ultrasonic oscillator with acetone solution for 10-20 minutes, and then the same operation is performed with anhydrous ethanol, and finally the materials are blown dry for later use. 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy material is converted into corresponding weight according to atomic percentage and each metal component is weighed.
[0033] Step 2: (1) Place the materials weighed in step 1 into the copper crucible of the WK-Ⅱ vacuum arc furnace in the order of increasing melting point. At the same time, polish the pure titanium ingots with 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh sandpapers and place them in the middle of the vacuum furnace. Then close and lock the furnace door. (2) First, use a mechanical pump to evacuate the arc furnace. When the vacuum gauge reading is less than 5 Pa, use a molecular pump to evacuate to 3×10 -4 Pa, and then slowly fill with argon until the pressure value is close to 0, and then use the mechanical pump and molecular pump to adjust the vacuum degree of the arc furnace to 3×10 -4 Pa. This process is repeated 3 times. (3) After the vacuum is completed, argon is slowly introduced for the last time until the pressure in the furnace is -0.03Mpa. Before the formal smelting of the high entropy alloy, the pure titanium ingot is melted 4 times, with the current controlled at 150A and the time being 120s. After each smelting, the pure titanium ingot is turned over for the next smelting. (4) The high entropy alloy material is melted at an arc current of 220A for 60s. During the smelting process, the arc rod is slightly rotated to ensure that the material is heated evenly.
[0034] Step 3: Repeat the smelting process 5 times according to step 2 to ensure uniform composition. After cooling for 20 minutes, remove the Al0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0035] Step 4: Al in step 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is subjected to aging heat treatment. (1) The smelted rod-shaped Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was homogenized at 1200℃ in an Ar atmosphere for 12h and water quenched. (2) The material in (1) was cold rolled to 80%, cut into 10×10×3mm standard specimens, annealed at 1100℃ for 10min and water quenched. (3) The specimen in (2) was aged at 750℃ for 1h and air cooled to obtain the final Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0036] The Al prepared in Example 1 0.4 FeNi 2.2 Cr 0.9 V 0.2 Phase structure analysis of high entropy alloys, such as Figure 1 As shown in the XRD pattern, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is mainly composed of FCC phase, and Ni3Al type precipitation phase also exists.
[0037] The Al prepared in Example 1 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy hardness test, according to Figure 3 It can be seen that Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 It has good hardness, with a hardness value of 300HV.
[0038] The Al prepared in Example 1 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was electrochemically tested to analyze its corrosion resistance in 3.5wt.% NaCl solution. Figure 5 As shown, Al 0.4FeNi 2.2 Cr 0.9 V 0.2 The potentiodynamic polarization curve of the high entropy alloy shows a wide range of passivation zone and a small corrosion current density, where the corrosion current density is about 9.681×10 -6 A / cm 2 .
[0039] Embodiment 2:
[0040] Preparation of Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, in which the atomic percentages of the elements are as follows: Al 8.5%, Fe 21.3%, Ni 46.8%, Cr 19.1%, V 4.3%.
[0041] Step 1: Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The materials for preparing high entropy alloy (Al material, Fe material, Ni material, Cr material, V material) are placed in glass beakers respectively, and firstly, they are cleaned by oscillating in an ultrasonic oscillator with acetone solution for 10-20 minutes, and then the same operation is performed with anhydrous ethanol, and finally the materials are blown dry for later use. 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy material is converted into corresponding weight according to atomic percentage and each metal component is weighed.
[0042] Step 2: (1) Place the materials weighed in step 1 into the copper crucible of the WK-Ⅱ vacuum arc furnace in the order of increasing melting point. At the same time, polish the pure titanium ingots with 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh sandpapers and place them in the middle of the vacuum furnace. Then close and lock the furnace door. (2) First, use a mechanical pump to evacuate the arc furnace. When the vacuum gauge reading is less than 5 Pa, use a molecular pump to evacuate to 3×10 -4 Pa, and then slowly fill with argon until the pressure value is close to 0, and then use the mechanical pump and molecular pump to adjust the vacuum degree of the arc furnace to 3×10 -4Pa. This process is repeated 3 times. (3) After the vacuum is completed, argon is slowly introduced for the last time until the pressure in the furnace is -0.03Mpa. Before the formal smelting of the high entropy alloy, the pure titanium ingot is melted 4 times, with the current controlled at 150A and the time being 120s. After each smelting, the pure titanium ingot is turned over for the next smelting. (4) The high entropy alloy material is melted at an arc current of 220A for 60s. During the smelting process, the arc rod is slightly rotated to ensure that the material is heated evenly.
[0043] Step 3: Repeat the smelting process 5 times according to step 2 to ensure uniform composition. After cooling for 20 minutes, remove the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0044] Step 4: Al in step 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is subjected to aging heat treatment. (1) The smelted rod-shaped Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was homogenized at 1200℃ in an Ar atmosphere for 12h and water quenched. (2) The material in (1) was cold rolled to 80%, cut into 10×10×3mm standard specimens, annealed at 1100℃ for 10min and water quenched. (3) The specimen in (2) was aged at 750℃ for 2h and air cooled to obtain the final Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0045] The Al prepared in Example 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 Phase structure analysis of high entropy alloys, such as Figure 1 As shown in the XRD pattern, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is mainly composed of FCC phase, and Ni3Al type precipitation phase also exists.
[0046] The Al prepared in Example 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy hardness test, according to Figure 3 It can be seen that Al 0.4 FeNi2.2 Cr 0.9 V 0.2 It has good hardness, with a hardness value of 320HV.
[0047] The Al prepared in Example 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was electrochemically tested to analyze its corrosion resistance in 3.5wt.% NaCl solution. Figure 5 As shown, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The potentiodynamic polarization curve of the high entropy alloy shows a wide range of passivation zone and a small corrosion current density, in which the corrosion current density is about 5.710×10 -6 A / cm 2 .
[0048] Embodiment 3:
[0049] Preparation of Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, in which the atomic percentages of the elements are as follows: Al 8.5%, Fe 21.3%, Ni 46.8%, Cr 19.1%, V 4.3%.
[0050] Step 1: Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The materials for preparing high entropy alloy (Al material, Fe material, Ni material, Cr material, V material) are placed in glass beakers respectively, and firstly, they are cleaned by oscillating in an ultrasonic oscillator with acetone solution for 10-20 minutes, and then the same operation is performed with anhydrous ethanol, and finally the materials are blown dry for later use. 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy material is converted into corresponding weight according to atomic percentage and each metal component is weighed.
[0051] Step 2: (1) Place the materials weighed in step 1 into the copper crucible of the WK-Ⅱ vacuum arc furnace in the order of increasing melting point. At the same time, polish the pure titanium ingots with 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh sandpapers and place them in the middle of the vacuum furnace. Then close and lock the furnace door. (2) First, use a mechanical pump to evacuate the arc furnace. When the vacuum gauge reading is less than 5 Pa, use a molecular pump to evacuate to 3×10-4 Pa, and then slowly fill with argon until the pressure value is close to 0, and then use the mechanical pump and molecular pump to adjust the vacuum degree of the arc furnace to 3×10 -4 Pa. This process is repeated 3 times. (3) After the vacuum is completed, argon is slowly introduced for the last time until the pressure in the furnace is -0.03Mpa. Before the formal smelting of the high entropy alloy, the pure titanium ingot is melted 4 times, with the current controlled at 150A and the time being 120s. After each smelting, the pure titanium ingot is turned over for the next smelting. (4) The high entropy alloy material is melted at an arc current of 220A for 60s. During the smelting process, the arc rod is slightly rotated to ensure that the material is heated evenly.
[0052] Step 3: Repeat the smelting process 5 times according to step 2 to ensure uniform composition. After cooling for 20 minutes, remove the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0053] Step 4: Al in step 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is subjected to aging heat treatment. (1) The smelted rod-shaped Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was homogenized at 1200℃ in an Ar gas atmosphere for 12h and water quenched. (2) The material in (1) was cold rolled to 80%, cut into 10×10×3mm standard specimens, annealed at 1100℃ for 10min and water quenched. (3) The specimen in (2) was aged at 750℃ for 4h and air cooled to obtain the final Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
[0054] The Al prepared in Example 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 Phase structure analysis of high entropy alloys, such as Figure 1 As shown in the XRD pattern, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy is mainly composed of FCC phase, and Ni3Al type precipitation phase also exists.
[0055] The Al prepared in Example 3 0.4 FeNi 2.2 Cr0.9 V 0.2 High entropy alloy hardness test, according to Figure 3 It can be seen that Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 It has good hardness, with a hardness value of 350HV.
[0056] The Al prepared in Example 3 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was electrochemically tested to analyze its corrosion resistance in 3.5wt.% NaCl solution. Figure 5 As shown, Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The potentiodynamic polarization curve of the high entropy alloy shows a wide range of passivation zone and a small corrosion current density, where the corrosion current density is about 9.348×10 -7 A / cm 2 .
[0057] From the above examples, it can be seen that the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloys exhibit excellent corrosion resistance in seawater environments and have high hardness. 0.4 FeNi 2.2 Cr 0.9 V 0.2 The corrosion current density of high entropy alloy after aging for 4 hours is only 9.348×10 -7 A / cm 2 . It can be seen that aging treatment has a significant effect on improving the corrosion resistance of materials. Therefore, the present invention improves the performance of the material by adjusting the aging time, while avoiding the large-scale use of precious metals such as titanium, nickel, and molybdenum, thereby reducing the manufacturing cost of high-entropy alloys. The present invention provides a new design idea for the development of seawater corrosion-resistant high-entropy alloys, which has high economic value and research significance.
[0058] The parts and English abbreviations not described in detail in this embodiment are common knowledge in the industry and can be searched on the Internet, so they are not described here one by one.
[0059] The parts not described in the present invention can be realized by referring to the prior art.
[0060] It should be noted that all equivalent substitutions made by those skilled in the art under the guidance of the present invention should be within the protection scope of the present invention.
Claims
1. A corrosion-resistant Al-Fe-Ni-Cr-V high entropy alloy, characterized in that The high entropy alloy composition is Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 , including Al 8.5%, Fe 21.3%, Ni 46.8%, Cr 19.1%, and V4.3%.
2. According to the Al described in claim 1 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, characterized in that The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The phase composition characteristics of the high entropy alloy are FCC phase and Ni3Al type nano-precipitation phase, showing the characteristics of uniform dispersion distribution.
3. The Al according to claim 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, characterized in that The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloys have good hardness, with a hardness value of 300-350HV.
4. The Al according to claim 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy, characterized in that The Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy exhibits excellent corrosion resistance in 3.5wt.% NaCl solution, with a corrosion current density lower than 9.348×10 -7 A / cm 2 .
5. The Al according to claim 1 0.4 FeNi 2.2 Cr 0.9 V 0.2 A method for preparing a high entropy alloy, characterized in that The following steps are involved: Step 1, ultrasonic cleaning and material weighing: 0.4 FeNi 2.2 Cr 0.9 V 0.2 Preparation of high entropy alloy Al, Fe, Ni, Cr, and V are placed in containers respectively, and firstly cleaned by oscillating with acetone solution in an ultrasonic oscillating device for 10-20 minutes, and then the same operation is performed with anhydrous ethanol, and finally the materials are blown dry for use; the Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was converted into corresponding weight according to atomic percentage and weighed, including Al 8.5%, Fe 21.3%, Ni 46.8%, Cr19.1%, and V 4.3%; Step 2: Melting: Place the material in step 1 into a WK-Ⅱ vacuum arc furnace and use a mechanical and molecular pump to evacuate to 1-5×10 -4 Pa, and then slowly fill in argon gas to make the vacuum degree reach 1~5×104Pa, and adjust the vacuum degree of the arc furnace to 1~5×10 -4 Pa; repeat this process 3 times to ensure that there is no oxygen in the vacuum chamber. Finally, slowly introduce argon gas to -0.02~-0.05Mpa, and melt the material at an arc current of 180~300A for 50-100s; Step 3: Repeat the smelting several times according to the requirements of step 2 to ensure uniform composition, and cool for 10-30 minutes to obtain Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
6. The Al according to claim 2 0.4 FeNi 2.2 Cr 0.9 V 0.2 A heat treatment method for a high entropy alloy, characterized in that The following steps are involved: Step 1: melt the rod-shaped Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 The high entropy alloy was homogenized at 1200 °C for 12 h in an Ar atmosphere and then quenched in water; Step 2: cold-roll the material in step 1 to 80%, cut it into 10×10×3 mm standard samples, anneal it at 1100° C. for 10 min, and then water-quench it; Step 3: The samples in step 2 were aged at 750°C for 1 / 2 / 4 / 10 h respectively, and then air-cooled to obtain the final high-hardness and super-corrosion-resistant Al 0.4 FeNi 2.2 Cr 0.9 V 0.2 High entropy alloy.
Citation Information
Patent Citations
High-entropy alloy with high strength and toughness and preparation method thereof
CN105755324A
High-entropy alloy with good strength and toughness matching and preparation method of alloy
CN106086486A
Precipitation-strengthening type AlCrFeNiV system high-entropy alloy and preparation method thereof
CN108193088A
Preparation method for high-entropy alloy containing hard CrV phase
CN110512101A
Ultrahigh strength-plasticity matched high-entropy alloy and preparation method thereof
CN115449691A
